Characteristics of plasma spray coatings - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2018)
The characteristics of plasma spray coatings are directly related to the type of process applied (APS - atmospheric plasma spray, VPS - vacuum plasma spray, and SPS - suspension plasma spray), the characteristics of the powder and the powder deposition parameters. The properties of plasma spray coatings can be changed and adjusted depending on the operating conditions, i.e. the purpose of coatings. Applying the same powder in the deposition process can lead to coatings of different properties, depending on their purpose. If the deposited coating is intended for corrosion protection and biomedical application, it is necessary that the coating is compact. When the coating is deposited for the purpose of thermal insulation, it should be porous. Powder particles in the plasma are spherical liquid drops which, in collision with the substrate, form a lamellar structure of the coating. A higher degree of powder melting and a higher velocity of molten droplets lead to a denser structure of deposited layers. When colliding with the substrate, deposited particles transfer heat to a working part until cooling to ambient temperature. If the working part is cooled by compressed air, molten droplets solidify extremely quickly with columnar crystals in lamellae. The aim of this paper is to describe the influence of temperature and velocity of powder particles on the deformation and hardening of particles defined by the D/d ratio, chemical changes in molten particles as well as porosity, crystal changes, and internal stresses in coatings.